Synthesis and Characterization of Acrylamide-Based Anionic Copolymer and Investigation of Solution Properties - H. Jamshidi; A. Rabiee (Advances in Materials Science and Engineering)
The copolymer of acrylamide (AM) and 2-acrylamido-2-methyl-1-propane sulfonic acid (AMPS) was synthesized through radical solution polymerization by potassium persulfate as initiator. By changing the AMPS feed ratio from 10 to 70%, and keeping other reaction conditions constant, different copolymers were synthesized. The techniques of Fourier transform infrared (FTIR) and nuclear magnetic resonance (1H- 13C-NMR) spectroscopy were used for identification of functional groups and confirmation of copolymers’ structure. Intrinsic and apparent viscosity of samples were measured in aqueous sodium chloride solution under standard conditions. The anionic degree of copolymers was determined by back titration method and by 13C-NMR spectroscopy. Molecular weight of copolymers was determined by the Mark-Houwink relationship. The measured molecular weight of samples showed that we have acquired a high molecular weight product. The effect of different range of shear rates on solution viscosity was evaluated. The copolymer solutions showed non-Newtonian shear thinning behavior. The performance of copolymers with respect to shear resistance and molecular weight was evaluated from industry application standpoint.